l-Arginine Induces White Adipose Tissue Browning-A New Pharmaceutical Alternative to Cold - Andjelika Kalezic; Aleksandra Korac; Bato Korac; Aleksandra Jankovic (MDPI AG, 2022)
The beneficial effects of l-arginine supplementation in obesity and type II diabetes involve white adipose tissue (WAT) reduction and increased substrate oxidation. We aimed to test the potential of l-arginine to induce WAT browning. Therefore, the molecular basis of browning was investigated in retroperitoneal WAT (rpWAT) of rats exposed to cold or treated with 2.25% l-arginine for 1, 3, and 7 days. Compared to untreated control, levels of inducible nitric oxide (NO) synthase protein expression and NO signaling increased in both cold-exposed and l-arginine-treated groups. These increases coincided with the appearance of multilocular adipocytes and increased expression levels of uncoupling protein 1 (UCP1), thermogenic and beige adipocyte-specific genes (Cidea, Cd137, and Tmem26), mitochondriogenesis markers (peroxisome proliferator-activated receptor (PPAR)-γ coactivator-1α, mitochondrial DNA copy number), nuclear respiratory factor 1, PPARα and their respective downstream lipid oxidation enzymes after l-arginine treatment. Such browning phenotype in the l-arginine-treated group was concordant with end-course decreases in leptinaemia, rpWAT mass, and body weight. In conclusion, l-arginine mimics cold-mediated increases in NO signaling in rpWAT and induces molecular and structural fingerprints of rpWAT browning. The results endorse l-arginine as a pharmaceutical alternative to cold exposure, which could be of great interest in obesity and associated metabolic diseases.